The gas-phase treatment of rubberwood / Suhaimi Muhammed - Muhammed, Suhaimi (Universiti Teknologi MARA Cawangan Pahang, 2002)
Rubberwood (Hevea brasiliensis) was treated with gaseous trimethyl borate [(Me03)B] and with gaseous trimethyl borate-methanol azeotrope [(MeO)3B-MeOH] for reasons of greater ease of penetration, relative homogeneity, and high transport rate. The trimethyl borate-methanol azeotrope gave better impregnation and relatively higher boric acid concentration. The concentration of boric acid is greater at the periphery of the wood and decreases rapidly towards the centre. The use of the trimethyl borate-methanol azeotrope might be commercially feasible as it uses cheap starting materials and gives good impregnation.